Editorial: Human Protein Kinases: Development of Small-Molecule Therapies - Alison D. Axtman (Kinases and Phosphatases)
Human protein kinases are ubiquitously expressed throughout the human body and embedded in signaling pathways that mediate diverse biology [...]